PENDAFTARAN MEREK ASOSIASI SEBAGAI MEREK KOLEKTIF (KAJIAN TERHADAP ASOSIASI RAJUT INDONESIA WILAYAH JAWA TENGAH) - Yudhitiya Dyah Sukmadewi (Universitas Semarang, 2017)
This study examines the registration of collective marks owned by theAssociation of Knitting Indonesia Central Java (Java ARI) on the knitting craftproducts manufactured and marketed independently. In addition, the assessmentconducted on the mechanism of collective trademark registration in the relevantinstitutions. The research method used juridical empirical approach. Juridicalaspect is based on Law No.20 of 2016 on Marks and Geographical Indicationsand related legislation, while reviewing the empirical aspects of the businessactivities carried on ARI Java. The results showed that ARI Java brand label havemet the brand element that can be registered as a collective trademarkregistration with domicile at the Directorate General of Intellectual Property ofthe Ministry of Law and Human Rights in Central Java.